PENYAIR-PENYAIR MALUKU UTARA - Rahma Djumati; Nurfani Nurfani (Humano: Jurnal Penelitian, 2022)
A poetis is an author of poetry, rhymes, and prose. The world of literature has developed along with the development of life in Indonesia. The large number of residents has led to the development of various events which is in turn the poets known by theirtrack records of prose and poetry. Of course, this existence is a good news for Indonesia in which it is rich in literature lovers. Then, by its love of literature a refined and noble character will grow. Behind of that, the growth of literary lovers is accompanied by the growth of writers that are poets, essays, short stories, poetry that showed contributing to the world of Indonesian literatures. Not a few good literary works that obey received positive appreciation by the government, which later emerged as regional writers because of their works. Nowadays, in North Maluku, many literature writers appear with their literary works. Therefore, poets must be known by the general public and education world. This study discusses about identification of poets originated from North Maluku region by conducting a qualitative descriptive research method to process data using the words instead of numbers and applying analytical tools, namely an expressive approach to see the biography of poets.